The Sentimental Education of the Novel - Cohen, Margaret, 1958- (Book collections on Project MUSE., 1999)
"Cohen draws on archival research, resurrecting scores of forgotten nineteenth-century novels, to demonstrate that the codes most closely identified with realism were actually the invention of sentimentality, a powerful aesthetic of emerging liberal-democratic society, although Balzac and Stendhal trivialized sentimental works by associating them with "frivolous" women writers and readers."--Jacket